A correlational gender study on I.Q. and emotional maturity quotient among college students - Napari, Odhella Corazon L. (Odhella Corazon L. Napari, 1999)
Man's effective adjustment with his environment is a function of his intelligence and ability to control his emotions, strife for survival, and his ability to be bonded and maintain good social relationships. This study is concerned with the relatedness of I.Q. and Emotional Maturity Quotient through correlation of scores and tests whether there are significant differences in the I.Q. levels and emotionality of men and women.